DISTRIBUSI KEGANASAN NASOFARING BERDASARKAN PEMERIKSAAN HISTOPATOLOGI PADA RUMAH SAKIT DI KOTA PEKANBARU TAHUN 2009-2013 - Alni Diniati; Wiwit Ade Fidiawati; Harianto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTNasopharyngeal carcinoma is a malignant tumor derived from epithelial cells in the nasopharynx. The rates of nasopharyngeal carcinoma has increased in the region of the head and neck. In 2010, nasopharyngeal carcinoma ranks 5th out of 10th. This study is descriptive with retrospective design that aimed to determine the distribution of nasopharyngeal carcinoma at hospitals in Pekanbaru from 2009-2013. The data collected from anatomical pathology laboratory center and hospitals in Pekanbaru, including: gender, age, histopathologic types and occupation. The result showed that there was 199 cases of nasopharyngeal carcinoma with the highest case found in 2013 were 92 (24,6%). The highest case found in Arifin Achmad Hospital were 92 (46,2%) and the lowest rates was in the Army hospital and Bhayangkara with 1 (0.5%) case. Nasopharyngeal carcinoma mostly infected male 130 (65,3%) cases than female 69 (34,7%) cases. The age range of 45-54 years had 56 (28.1%) cases. Most of histopathologic types had found in the type of undifferentiated carcinoma (WHO type III) as many as 136 (68,3%) cases. The most occupation is farmer and housewifes as many as 32 (16.1%) cases.Key words : nasopharyngeal carcinoma, distribution, histopathologic type.